Vagueness in Philosophy -- "Unbestimmtheit" in Physics - Pirner, Hans J. (Technische Universität Dortmund, 2010)
Unbestimmtheit is discussed with three connotations: indefiniteness-vagueness, uncertainty and indeterminacy. Vagueness is a term in philosophy, the two other meanings are found in physics. I will study several physics cases: experimental errors, natural borderline cases, quantum indeterminacy, uncertainty and indeterminacy in statistical and stochastic physics. Characteristically, the three classes are often found to be mixed. A very sketchy discussion concludes the article: How should one handle Unbestimmtheit? When and how should one clarify, classify, define limits, use fuzzy logic?
Physics & Philosophy ; 14
Keywords: experimental uncertainty; fuzzy logic; indefiniteness; indeterminacy; physics borderline cases; quantum indeterminacy; quantum logic; stochastic and random physics; uncertainty; Vagueness; 100; 530